Cloning and expression of Rubisco Like Protein (RLP) from halophilic bacterium Chromohalobacter salexigens BKL 5 - IRWAN SUDARMANTO; LINCE SITOHANG; SAIFUR ROHMAN; WAYAN TUNAS ARTAMA (Society for Indonesian Biodiversity, 2024)
Abstract. Sudarmanto I, Sitohang L, Rohman S, Artama WT. 2024. Cloning and expression of Rubisco Like Protein (RLP) from halophilic bacterium Chromohalobacter salexigens BKL 5. Biodiversitas 25: 1605-1614. This research seeks to identify and determine the Rubisco-like protein characteristics from Chromohalobacter salexigens BKL 5 tested using a recombinant method approach. C. salexigens BKL 5 is a halophilic bacterium found in Bledug Kuwu Mud, Central Java. The Open Reading Frame (ORF) gene encoding Rubisco-like protein from that bacterium was successfully amplified using the polymerase chain reaction method using the primers we designed. Cloning of that gene on the pCold plasmid was carried out using the double digest method with the restriction enzymes NdeI and EcoRI. The results of plasmid transformation in Escherichia coli BL 21 were successful, indicating that the bacterial culture was grown in Luria Bertoni agar media containing the antibiotic ampicillin. Overexpression protein of the transformed Escherichia coli BL 21 shows that the effective temperature that produces maximum results is 16°C. The results of sequencing and phylogenetic analysis showed that the protein belongs to the Rubisco family, namely Rubisco-like protein with a residue of 429 amino acids and a weight of 46 kDa. Prediction of 3D structures using the Alphafold tool gives an accuracy above 90%. Observation of the 3D structure shows that glutamic acid is more distributed on the surface of the protein which is important for protein solubility. Tests with SOPMA showed that this protein was dominated by random coil structure of 41.96% which was identical to that found in bacterial species in extreme habitats. The dynamic molecular analysis using Yasara at 10 ns showed that the protein had a tendency to undergo considerable deformation but remained stable.